Bundesstaat und Europäische Union zwischen Konflikt und Kooperation : Berichte und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Rostock vom 4. bis 7. Oktober 2006 - Kadelbach, Stefan; Pieroth, Bodo (De Gruyter Recht, 2007)
The volume presents the reports and discussions held at the conference of the "Association of German Constitutional Law Teachers" in Rostock from October,4th to October 7th,2006.
Keywords: European Union -- Congresses.; Federal government -- European Union countries -- Congresses.; Constitutional law -- European Union countries -- Congresses.; Central-local government relations -- European Union countries -- Congresses.; European federation -- Congresses.; LAW -- Government -- General.; European Union.; Central-local government relations.; Constitutional law.; European federation.; Federal government.; European Union countries.; Electronic books.; Conference papers and proceedings.